ROSELLA (Hibiscus sabdariffa) SEBAGAI ALTERNATIF BAHAN PEWARNA HISTOLOGI - Yeni Rahmawati; Saraswati Saraswati (Akademi Kesehatan John Paul II Pekanbaru, 2023)
ABSTRACT Hematoxylin-Eosin (HE) is a synthetic dye that is commonly used in histological examination. HE exposure in the long term has a negative impact on health. The development of alternative dyes is important. Therefore this literature study aims to determine the use of rosella (Hibiscus sabdariffa) in histological staining. Literature review was conducted from five data sources, namely Google Scholar, Medline, Oxford Academic, Research Gate and Science Direct. Based on a literature search, 10 journals were obtained which showed that rosella (Hibiscus sabdariffa) can be used as an alternative dye for various types of human or animal histological tissues. Extraction can be done on fresh or dry leaves and flower petals. Solvents that can be used in the extraction process are polar solvents, namely distilled water or alcohol. Extraction methods of soxhletation, reflux, maceration or boiling can be used in the extraction of rosella (Hibiscus sabdariffa). Staining can be done using pure or modified extracts. Various variations of extraction methods, types of solvents, concentrations and staining times, as well as the degree of acidity performed can give staining results that are as good as HE. Rosella (Hibiscus sabdariffa) can be used as an alternative to HE dye. Keywords: Rosella, Hematoxylin Eosin, staining, histology